Hubungan Antara Disiplin Belajar Dengan Tanggung Jawab Siswa Dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama Negeri 43 Pekanbaru - Mardatillah, Nur Aprilda; Risnawati, Risnawati; Hamdani, M. Fikri (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the relationship between learning discipline and student responsibility in learning Islamic Religious Education (PAI) at SMP Negeri 43 Pekanbaru. This research used quantitative approach with correlational method. The sample amounted to 65 students who were taken using simple random sampling technique from a total population of 186 students. The instrument used is a Likert scale questionnaire that has been tested for validity and reliability. The results of data analysis using the Pearson Product Moment correlation test showed a correlation coefficient value of 0.740 with a significance of 0.000 <0.05. This shows that there is a positive and significant relationship between learning discipline and student responsibility in PAI learning. Thus, the higher the students' learning discipline, the higher the students' responsibility. This relationship is in the strong category.